جماليات التجريب في روايتي "ضو البيت ومريود" للطّيب صالح - بسمة علية- عائشة الوحيد- عبد المجيد مازوزي (University of El-Oued جامعة الوادي, 2025)
ملخص: عربي تهدف هذه الدّراسة إلى كشف جماليات التّجريب كسمة سردية حداثية في الرّواية العربية،وذلك من خلال تحليل روايتي "ضوء البيت" و"مريود" للكاتب السوداني طيب صالح. باعتماد هيكل تنظيمي للمذكرة من مدخل للموضوع، ثمّ فصل نظري يناقش قضية التّجريب في السّرد من حيث المفهوم والبوادر والتّجليات، ثمّفصل تطبيقي تتبعنا فيه مظاهر ومستويات التّجريب عند الرّوائي وفق منهج نقدي تحليلي، توصلنا إلى أنّ للتّجريب في سرديات طيب صالح جمالية تجمع بين التزامه وإبداعية التّشكيل، والمتخيّل السّردي. This study sought to discover the aesthetics of experimentation as a modernist narrative trait in the Arabic novel, through the two novels analysis "Light the House" and "Marioud", by the Sudanese writer Tayeb Saleh. It was based on a structured format that begins with an introduction to the topic, followed by a theoretical chapter that discusses the concept, origins, and manifestations of experimentation in narrative, and a fieldwork chapter in which we trace the forms and levels of experimentation in the author's work using a critical analytical approach. The findings showed that experimentation in Tayeb Saleh’s narratives embodies an aesthetic that combines commitment with creative formation and narrative imagination.
مذكرة .ماستر النقد الحديث والمعاصر. 2025
Keywords: الرّواية، التّجريب، الطيب صالح، ضو البيت، مريود; Novel; Arabic novel; experimentation; Tayeb Saleh; Light the House; Marioud.